VISUAL MODELS OF DYNAMIC DATA STRUCTURES AND THEIR IMPORTANCE IN TEACHING PROGRAMMING - STOFFOVÁ, Veronika; Ladislav, VÉGH (Trends in education, 2013)
The article deals with the description of visual models of standard dynamic data structures, which allows creating the right idea of their implementation in the memory of computers. The right idea of creating dynamic variables and dynamic data structures is closely related to the notion of dynamic allocation of memory. The right understanding of structure and construction of dynamic data structures allows comprehending rules of accessing elements in structures, possibilities of implementing basic operations and functions related to structures. The models are based on the linear structure of memory (i. e. memory is viewed as an ordered set of addressable units - bytes or the units of more bytes). In the last part of this article is described a didactic application which helps understanding basic operations on single lined dynamic data structures.
Keywords: dynamic variable; dynamic data structures; teaching programming